Refleksi Konsep Akuntansi Lingkungan dari Tradisi Sasi - Fadli F. Malawat; Arizal Hamizar; Fanji Farman; Fatmah Watty Pelupessy; Afdhal Yaman (Journal of Business Application, 2024)
his study aims to reflect on the concept of environmental accounting based on the Sasi tradition, a local wisdom of the Maluku community, to support sustainable natural resource management. The study also explores the integration of cultural and spiritual values into the modern concept of environmental accounting, which is expected to provide solutions to global challenges related to environmental issues. A qualitative method was used with an ethnographic approach to uncover the meanings and values embedded in the Sasi tradition. Data were collected through literature reviews, analysis of customary law documents, and relevant case studies. A multidisciplinary approach combining accounting, anthropology, and ecology was applied to analyze this tradition in the context of sustainability. The analysis was conducted descriptively and interpretatively, highlighting the principles of the Sasi tradition and their relevance in developing more inclusive environmental accounting. The findings show that the Sasi tradition reflects sustainability principles aligned with the triple bottom line theory, encompassing social, economic, and environmental aspects. The spiritual and cultural values in this tradition, such as responsibility to God, nature, and fellow humans, provide a strong conceptual framework for application in environmental accounting.